ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM KEPUTUSAN MEMBELI RUMAH SEDERHANA DI PERUMAHAN PURIMAS KELURAHAN BENTIRING KECAMATAN MUARA BANGKA HULU KOTA BENGKULU - Markoni Markoni (Creative Research Management Journal, 2018)
This study aims to determine the effect of Price, House Design, location, available facilities, and Housing Environment simultaneously on consumer behavior in the decision to buy a simple house in Purimas Housing, Bentiring Sub-District, Bengkulu City Muara Bangka Hulu Subdistrict, and which factors have partial influence more dominant. The population of this study was buyers of simple houses in Purimas Housing, Bentiring Sub-District, Muara Bangka Hulu Sub-District, bengkulu City. Sampling uses incidental sampling techniques. Data collection uses questionnaires and literature. Primary data and secondary data collected, processed and analyzed by multiple correlation methods and multiple linear regression methods. Price Factors, House Design, location, facilities available, and Housing Environment simultaneously have a very strong influence on consumer behavior in simple home buying decisions in Purimas housing as indicated by the multiple correlation coefficient (R) 0.929, with the contribution of variations to the fifth change in the independent factor for consumer behavior by 86.3%. From the equation Y = 0.079 + 0.267X1 + 0.202X2 + 0.175X3 + 0.192X4 + 0.218X5 + e1 By comparing the magnitude of the Regression coefficient of each Price Factor, Design, Location, Available Facilities and environment, it is known that the more dominant factor influencing consumer behavior is the price of the house, then followed by the environment, design and then available facilities and housing locations. Hypothesis Test Results on multiple correlation coefficients, as well as Hypothesis Tests on regression coefficients of all the Factors studied show that there is a significant effect of Price Factors, House Design, location, available Facilities, and Housing Environment both simultaneously and partially significantly influence towards consumer behavior in the decision to buy a simple house in Purimas Housing, Bengkulu City. Based on the analysis, the researcher suggested the developer company to maintain prices, create new designs that follow market tastes, and improve housing facilities.